1991
DOI: 10.1063/1.461119
|View full text |Cite
|
Sign up to set email alerts
|

Probing icy surfaces with the dangling-OH-mode absorption: Large ice clusters and microporous amorphous ice

Abstract: Infrared absorption bands that have previously been assigned to vibrations of the dangling bonds (db) of water molecules at the surfaces of crystalline ice clusters and the micropores of amorphous ice have been investigated to determine their usefulness in probing molecular-level events at icy surfaces. This study has established that the db bands are sensitive to adsorption of gases at the cluster or micropore surfaces, and that reversible adsorption/desorption at the db sites is readily monitored spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
154
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(160 citation statements)
references
References 15 publications
5
154
1
Order By: Relevance
“…For example, the study of the adsorption of hydrogen and nitrogen on NCI by Rowland et al has revealed red shifts of 10 cm -1 in these dangling-bond features for doubly coordinated and triply coordinated adsorption sites. 13 In the case when strong H-bonding is involved in the adsorption of a guest species, the red shift in the OH dangling bond is expected to increase. 12 The weak OH dangling-bond feature for a guest species (e.g., acetone) upon adsorption on ice could then be obscured by the much stronger OH stretch feature of the bulk if the magnitude of the red-shift happens to be large.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the study of the adsorption of hydrogen and nitrogen on NCI by Rowland et al has revealed red shifts of 10 cm -1 in these dangling-bond features for doubly coordinated and triply coordinated adsorption sites. 13 In the case when strong H-bonding is involved in the adsorption of a guest species, the red shift in the OH dangling bond is expected to increase. 12 The weak OH dangling-bond feature for a guest species (e.g., acetone) upon adsorption on ice could then be obscured by the much stronger OH stretch feature of the bulk if the magnitude of the red-shift happens to be large.…”
Section: Introductionmentioning
confidence: 99%
“…Two small features are also present on the wing of the O-H stretching modes band, whose peak positions are at 3720 and 3697 cm −1 (2.69 and 2.70 µm, respectively). These weak bands come from O-H dangling bonds in the micropores of the porous structure of amorphous water ice (e.g., Rowland et al 1991;Palumbo 2006). By warming up amorphous water-ice, a more ordered (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…If this sample is warmed up, at about 30 K, N 2 diffusion in the porous structure of solid water takes place. The diffusion is proven by the shift of the O-H dangling bonds features from 3697 to 3672 cm −1 and from 3720 to 3690 cm −1 (Rowland et al 1991;Palumbo & Strazzulla 2003). Furthermore, Palumbo & Strazzulla (2003) have shown that a band at 5300 cm −1 appears after diffusion of N 2 in porous amorphous solid water.…”
Section: Diffusion Of N 2 In H 2 Omentioning
confidence: 98%
See 2 more Smart Citations